Possible electronic decay channels in the ionization spectra of small clusters composed of Ar and Xe: a four-component relativistic treatment - Faßhauer, Elke; Kryzhevoi, Nikolai V.; Pernpointner, Markus (The journal of chemical physics, 2010)
Electronic decay of the inner-valence Ar 3s−1 vacancy is energetically forbidden in an isolated argon atom and in all rare gas dimers where argon is present. However, if an argon atom has at least two suitable rare gas atoms in its neighborhood, the Ar 3s−1 vacancy may decay electronically via an electron transfer mediated decay (ETMD) mechanism. An ArXe2 cluster is considered in the present paper as an example of such systems. The single and double ionization spectra of different ArXe2 isomers as well as of homonuclear Ar2 and Xe2 and heteronuclear ArXe clusters have been calculated by means of propagator methods to reveal possible electronic decay channels. A four-component version of the one-particle propagator utilizing the Dirac-Coulomb Hamiltonian was employed to obtain the single ionization potentials of the clusters studied. Hereby electron correlation, scalar relativistic effects, and spin-orbit couplings are described in a consistent manner. A two-particle propagator in its one-component form, in conjunction with effective core potentials to account consistently for correlation and scalar relativistic effects, was used to calculate the double ionization potentials. ETMD is shown to be the only possible electronic decay process of the Ar 3s−1 vacancy in the ArXe2 cluster. In clusters with more Xe atoms, alternative electronic decay mechanisms may appear.
Gesehen am 12.06.2023